Purple Sweet Potato Flour Substitution And Fermentation Time In White Bread Modification - Miranti; Muji Paramuji; Barus, Wan Bahroni Jiwar; M. Nuh; Faridhil Wafiq (Talenta Publisher, 2024)
The rapid development of noodle consumption in Indonesia provides this lesson that noodles are a type of food by needs or favorite Indonesian consumers, it could even be said that noodles have become an alternative food main after rice. The management of purple sweet potatoes is another alternative to consuming carbohydrates so that they can be processed into food products such as bread, pasta, noodles instant, etc. Utilization of sweet potatoes purple can also be substituted with wheat flour and is the first step in reducing the consumption of wheat flour, remembering that Indonesia is not a wheat-producing country which is the raw material for wheat flour, so it is an advantage because No need to import flour wheat. This research aims to find the best substitution for purple sweet potato with wheat flour and the best drying temperature in producing modified dry noodles. The design model used in this research was a completely randomized design (RAL) factorial consisting of two factors that is: Factor I (U = Substitution of purple sweet potato with wheat flour) consisted of 4 treatments namely: U1 (20%:80%), U2 (30%:70%), U3 (40%:60%), and U4 (50%:50%). Factor II (S = Drying Temperature) consists of 4 treatments, namely: S1 (65° C), S2 (70° C), S3 (75° C) and S4 (80° C). The parameter observed consists of rate water, rate ash, rate fat, organoleptic texture, taste, and color. The results of the research show that the substitution of purple sweet potato with wheat flour is influential and very significant (P>0.01) to rate water, rate ash, organoleptic texture, taste, and color but the effect is not significant (P<0.05) to rate fat. Temperature drying influences different very significantly (P>0.01) to rate water and rate ash. However influential no significant (P<0.05) on fat content, organoleptic texture, taste, and color. Interaction treatment is influential with no significance (P<0.05) for all parameters analyzed. To obtain noodles dry sweet potato purple which is quality good recommended for use 20% sweet potato purple, 80% flour wheat, and temperature drying 80° C.